Using rubrics for assessing information literacy in the finance classroom: A collaboration. Issue 2 (2nd April 2016) - Mezick, Elizabeth M.; Hiris, Lorene
ABSTRACT: Business information literacy (BIL) is a core competency for lifelong learning and critical to achieving professional success. This article reports on the evolution of a collaborative framework for integrating and assessing information literacy in subject-specific upper-level undergraduate, as well as introductory MBA, courses in finance. The framework, developed over a significant period of time, provides a guide for structured and full collaboration between librarians and classroom instructors and includes a sample assignment and accompanying evaluation rubric which are adaptable across disciplines. Additionally, it provides a model for developing pedagogical methodologies for student attainment of BIL competencies and for faculty assessment of them.